2010
DOI: 10.1371/journal.pone.0013487
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Fish Oil and Montelukast and Their Combination on Airway Inflammation and Hyperpnea-Induced Bronchoconstriction

Abstract: BackgroundBoth fish oil and montelukast have been shown to reduce the severity of exercise-induced bronchoconstriction (EIB). The purpose of this study was to compare the effects of fish oil and montelukast, alone and in combination, on airway inflammation and bronchoconstriction induced by eucapnic voluntary hyperpnea (EVH) in asthmatics.MethodsIn this model of EIB, twenty asthmatic subjects with documented hyperpnea-induced bronchoconstriction (HIB) entered a randomized double-blind trial. All subjects enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
34
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 58 publications
10
34
1
1
Order By: Relevance
“…6,18 The most obvious diff erence is that we used inhaled mannitol, a bronchial provocation challenge that has been derived from the understanding of the eff ects of dry air hyperpnea-induced BHR, which is a well-established alternative challenge stimulus to study EIB. There is strong evidence that the airway response to mannitol closely mimics central components of EIB, such as the activation of mast cells and eosinophils, resulting in the release of bronchoconstrictive mediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,18 The most obvious diff erence is that we used inhaled mannitol, a bronchial provocation challenge that has been derived from the understanding of the eff ects of dry air hyperpnea-induced BHR, which is a well-established alternative challenge stimulus to study EIB. There is strong evidence that the airway response to mannitol closely mimics central components of EIB, such as the activation of mast cells and eosinophils, resulting in the release of bronchoconstrictive mediators.…”
Section: Discussionmentioning
confidence: 99%
“…3 More recently, 3 weeks of omega-3s were reported to inhibit mild airway responses to exercise and eucapnic voluntary hyperventilation (EVH) in both elite athletes and symptomatic subjects with asthma. [4][5][6] Th is was observed in association with reductions in markers of airway infl ammation, such as reduced cytokine levels, reduced excretion of the urinary eicosanoids 11 b -prostaglandin F2 a (11 b -PGF 2 a ) and leukotriene E4 (LTE 4 ), and decreased sputum eosinophil counts, suggesting that the benefi ts of an omega-3-enriched diet on EIB was through antiinfl ammatory mechanisms.…”
mentioning
confidence: 99%
“…Mickleborough and colleagues have demonstrated the protective effects of fish oil on exercise induced bronchoconstriction in asthmatic populations (Mickleborough et al 2006;Mickleborough et al 2003). In addition, Tecklenburg-Lund et al (2010) reduced airway inflammation in asthmatic subjects following a 3wk period of fish oil supplementation (Tecklenburg-Lund et al 2010). However, to date, it is unknown if fish oil supplementation for a similar 3 wk period will mitigate the airway inflammatory response elicited by a single HFM.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the possibility exists for drug-diet interactions that confer greater anti-inflammatory benefits in the airway than either intervention alone. However, Tecklenburg-Lund et al (37) have shown recently that, whereas both fish oil and montelukast (Singulair A , Merck & Co., Inc., Whitehouse Station, NJ) taken in isolation are effective in attenuating airway inflammation and hyperpnea-induced bronchoconstriction in asthmatic subjects, treatment of both these agents in combination does not provide a greater anti-inflammatory effect or suppression of hyperpnea-induced bronchoconstriction than either treatment alone. On the basis of the available evidence (24,26,28,37), it is clear that fish oil supplementation should be considered an alternative treatment for exercise-induced bronchoconstriction.…”
Section: Fish Oil Supplementationmentioning
confidence: 99%